Optimization of Formula, Stability Testing, and Antioxidant Activity of Clay Masks as Skin Moisturizers - Widyaningrum, Naniek; Anggoro Bhakti, Agung Dwi; Evan Maulana, Alghafiqy Harya; Safitri, Amalia; Ramadhani, Adinda Fajrah; Febriani, Anisa; Hanafi, Anggit Naufal; Arief, Thendi Abdul (Pharmaceutical Sciences and Research, 2025)
Clay masks are cosmetic formulations designed to adhere closely to the skin, effectively lifting contaminants, cleansing the face, and absorbing impurities. We made a clay mask containing active ingredients such as niacinamide, alpha arbutin, ceramide, and hyaluronic acid. A careful selection of ingredients is essential for ensuring safety and mitigating potential dermatological issues. This study aimed to evaluate the physical characteristics, stability, primary irritation potential, and moisturizing efficacy of this clay mask formulation. Kaolin and bentonite are the primary base materials. The research included formulation optimization and physical stability testing using a cycling test, where each cycle was conducted over a 24-hour period for a total of six cycles. Evaluations were performed on organoleptic properties, homogeneity, pH, spreadability, viscosity, and drying time. Subsequently, data were analyzed using paired sample T-tests. Antioxidant activity was assessed using the ABTS method to determine IC50 values. Both preclinical and clinical irritation tests were performed, and the clinical efficacy of the moisturizer was evaluated in 30 participants. The optimal formula consisted of 0.8% kaolin and 0.2% bentonite, and all the evaluation parameters met the required standards. Stability testing and percentage inhibition measurements revealed no significant differences during storage (p>0.05). The formulation demonstrated strong antioxidant activity (IC50<50) and showed no irritation in preclinical or clinical irritation tests. The efficacy results indicated that the developed clay mask formulation has significant potential as a safe and effective skin moisturizer.